2016
DOI: 10.3390/s16040433
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Mechanical and Electrical Behavior of a Tuning Fork-Shaped Ionic Polymer Metal Composite Actuator with a Continuous Water Supply Mechanism

Abstract: This paper presents an innovative tuning fork-shaped ionic polymer metal composite (IPMC) actuator. With an integrated soft strain gauge and water supply mechanism (WSM), the surface strain of the actuator can be sensed in situ, and providing a continuous water supply maintains the water content inside the IPMC for long-term operation in air. The actuator was fabricated using a micromachining technique and plated with a nickel electrode. The device performance was experimentally characterized and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In this case, a laser or a camera captures the sample free end's movement, measuring its displacement as a function of time 19,20 . A remarkable way to investigate the electromechanical behavior of IPMC samples using video analysis frame by frame was proposed for several papers [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a laser or a camera captures the sample free end's movement, measuring its displacement as a function of time 19,20 . A remarkable way to investigate the electromechanical behavior of IPMC samples using video analysis frame by frame was proposed for several papers [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The current displayed a periodic variation with the peak current swiftly dropping from 66 mA to 33 mA (absolute value), thereby reaching a near steady-state value. This current property could be decomposed into faradic and non-faradic currents in each cycle [41,42]. The non-faradic current could be associated with current greater than the steady-state value (absolute value).…”
Section: Device Characterization and Discussionmentioning
confidence: 99%
“…This review article focuses on ionic polymermetal composites and their potential applications in tissue engineering. Recent research on EAPs has shown their potential in the development of versatile soft robots [8]. These soft robots with compliant bodies and flexible actuators have gained significant attention in various fields, including biomedical applications [9].…”
Section: Introductionmentioning
confidence: 99%